Free T3 as a Reliable Indicator of Thyroid Dysfunction in Cirrhosis - Shazia Shakoor; Fatima Shad Kaneez; Uzma Iftikhar (Philippine Association of Institutions for Research, Inc., 2012)
Liver cirrhosis is a common ailment afflicting a significant proportion of Pakistani population of all ages. Quite often, these patients require multi-system intervention, owing to the nature of this disease. This study was specifically conceived to objectively assess the level of thyroid dysfunction in cirrhotics of the urban population of Karachi, together with its relationship to the severity of liver malfunction as gauged by the Childs classification. Liver and thyroid hormones are intricately correlated so thyroid hormone abnormalities are seen in patients of liver diseases, although they are clinically euthyroid. The aim of this study is to correlate the abnormalities in thyroid hormones with the clinical staging of hepatic encephalopathy and to examine the role of thyroid hormone as a reliable prognostic indicator of encephalopathy. We assessed 50 patients of cirrhosis for the thyroid hormone levels (including thyroxine, triiodothyronine and TSH) by Enzyme Linked Immuno sorbent Assay (ELISA) technique. Patients were also examined clinically for gradings of Cirrhosis by The Childs Pugh classification. All procedures on patients were done in accordance with the Helsinki Declaration. Triiodothyronine (FT3) was found to be a useful indicator of thyroid dysfunctions and it parallels the grading of Childs classification, whereas thyroxine and TSH were not found to be significantly correlated. We proposed that triiodothyronine could act as a prognostic marker to predict severity of cirrhosis and for assessing minimal hepatic encephalopathy.